NON-TECHNICAL SKILL ADVISABLE AND ACTUAL SITUATION ANALYSIS - Bankovičs, Arnis; Ivaņinoka, Ieva; Jansons, Andris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
essential high-risk professions component is non-technical skills - human cognitive and social skill set. These skills gets and are integrated together with technical skills. This paper is discussed in the context of the three groups - cognitive skills, social skills and personal resource management skills. Each group includes important non-technical skills, without which high-risk professions would be unable to achieve the objectives and fulfill the tasks excellently. One of the following professions is ship navigator. It is believed that these skills are actual direct performance of their duties and non-technical skills are good performance to characterized "the perfect ship navigator." Skills gap arises because insufficient attention is paid to this problem, and due to this the young ship navigators performance is affected negative. This paper aims to describe and analyze the current situation in the preparation of the young ship navigators and compare them with experienced captains results. For performing the tasks was used complex methods to analyze and assess the desired and the real situation in this profession.